English English - Husein Salahuddin; Moh. Fery Fauzi; Lailatul Mauludiyah (Jurnal Internasional Pendidikan Bahasa Arab, 2020)
This study was to determine the effectiveness of the kinemaster-based animated video to improve the vocabulary mastery of Arabic for eighth grade students at MTs. Nurul Huda Ketambul, Tuban, East Java.. This research used an associative quantitative approach. The population in this study was class VIII MTs Nurul Huda Ketambul, Tuban, which consisted of one class. The sample of this research was class VIII with a total of 21 students, and this study used a quota sample that only used one class in the study. While the research data collection was a test (pre test and post test) and a questionnaire. Analysis of the data used in this study aimed to determine the significant results of the instruments used. The results of the research on the effectiveness of the kinemaster-based animation video to improve the vocabulary mastery of Arabic for eighth grade students of MTs Nurul Huda Ketambul, Tuban, were effective in improving students' mastery of Arabic vocabulary, even though it was included in the medium category 56.60%. The categorization is based on Archambault's normalized Gain criteria table. This shows a significant value for the kinemaster-based animated video to improve students' mastery of Arabic vocabulary which proved to be quite effective.